EVALUASI USABILITY PADA APLIKASI ONLINE DISDUKCAPIL MENGGUNAKAN METODE WEBSITE USABILITY EVALUATION TOOL (WEBUSE) - Mariadi; Dian Prawira; Nurul Mutiah (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2023)
The development of technology acts as a means for government agencies to provide ease of service to the community. The application of technology in population administration services, for example, the Disdukcapil Online Application is a web-based application provided by the Pontianak City Population and Civil Registry Office to make it easier for people to access various services with online queue registration facilities, online services, and residents come. In implementing the Pontianak City Disdukcapil Online Application, there are several usability problems, namely difficult to access when the queue registration hours are opened, the number of quotas is always full when registering due to system problems, there are similarities in icons, and the color on the selected navbar menu does not change. Therefore, it is necessary to measure usability evaluation which aims to determine the level of usability in the Pontianak City Disdukcapil Online Application. The method used to measure the usability level of the Pontianak City Disdukcapil Online Application is the Website Usability Evaluation Tool (WEBUSE). Based on questionnaires distributed to the people of Pontianak City and residents came with a total of 100 respondents. The results of measuring usability evaluation using the WEBUSE method on the Pontianak City Disdukcapil Online Application get a usability point of 0.68 so that it is at the "Good" usability level. However, there are two attributes in the user interface design category at the "Moderate" usability level, namely UID1 and UID2 with the same usability point of 0.57. From the results of usability points that are below the threshold value, there are 18 attributes that are given recommendations for interface improvement.